MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS DENGAN MENGGUNAKAN METODE IMPROVE - Sukmadirja Sukmadirja; Hepsi Nindiasari; Abdul Fatah (Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to examine the improvement of Mathematical Reflective Thinking skills using the IMPROVE Method. The things that underlie the research are the low level of Mathematical Reflective Thinking skills of junior high school students, mathematics learning that has been implemented has not been able to improve mathematics learning and the need for learning processes that can develop students' Mathematical Reflective Thinking skills according to student characteristics. This study used a quasi-experimental method with pretest-posttest class group design. The study population was all eighth grade students of one of the junior high schools in Serang City. Sampling used a purposive random sampling technique so that 38 students as a group who received the IMPROVE learning method and 38 students obtained regular learning. The research instrument consisted of tests of mathematical reflective thinking skills and students' initial mathematical prior knowledge tests. Analysis of the data used was the difference test of the average t test, t test, and Mann Whitney U. The results showed that (1) there was an increase in Mathematical Reflective Thinking skills both overall and based on students' initial mathematical prior knowlegde using the IMPROVE Method; (2) There is no interaction between the learning models and the mathematical prior knowledge (high, medium, and low) towards improving students' mathematical reflective thinking skills.